Financial Restatements Consequences for Corporate Reputation and Investor Trust (gjstudies, 2022)
This research investigates the underexplored psychological and reputational mechanisms through which financial restatements erode investor trust, moving beyond traditional event-study methodologies to propose a novel, multi-dimensional framework.While prior literature predominantly quantifies market reactions through stock pricevolatility and trading volume, this study uniquely integrates concepts from behavioralfinance, organizational stigma theory, and communication studies to model the erosionof trust as a complex, non-linear process. We introduce the concept of ’reputational viscosity’—the resistance of a firm’s reputation to recover post-restatement—and developa composite index measuring its determinants. Through an original methodology combining computational text analysis of earnings call transcripts, experimental vignettestudies with institutional investors, and longitudinal analysis of media sentiment, wetrace the cascading effects of restatement disclosures. Our findings reveal that thenarrative framing of the restatement cause, the perceived integrity of the remediationresponse, and the pre-existing social capital of the firm interact in unexpected waysto determine long-term trust decay. Contrary to conventional wisdom, we find thattechnical, complex error restatements can be more damaging to sophisticated investortrust than fraud-induced restatements, due to heightened perceptions of managerialincompetence and systemic control failures. The study concludes by proposing a predictive model for trust restoration trajectories, offering a significant departure fromthe prevailing focus on punitive legal and financial outcomes, and providing managerswith a novel toolkit for reputational repair grounded in communicative transparencyand symbolic accountability actions.